Voronoi acoustic source localization mechanism based on counter captured time difference - Na XIA; Cheng-chun NI; Chao-nong XU; Sheng DING; Rong ZHENG (Tongxin xuebao)
An acoustic source localization protocol based on counter captured time difference was presented. It can drive the sensors in network to “sleep”in most of the time, so as to achieve energy saving obviously. In the stage of computing the acoustic source position with the time difference data, Voronoi diagram was introduced to reduce the searching space to improve the success percentage and convergence speed of the algorithm. Both the theoretical analysis and experiment results demonstrate that this acoustic localization mechanism is energy efficient, in real-time and robust in localization computing. So it is suitable for dynamic acoustic source accurate localization in WSNs.